The free education policy in Chile: Between transforming and maintaining neoliberalism - Rios-Jara, H. (South African Journal of Higher Education, 2023)
Free education policies usually represent the antithesis and the antidote toward the rising cost and the inequalities brought by fees and loans to higher education. But can free education policies transform neoliberalism in higher education? This article explores the transformative capacity of the free education policy introduced in Chile in 2016. The article examines the continuities and discontinuities between the higher education system before and after the introduction of the free education policy. The article exposes that the free education policy effectively increased public investment in the sector and reduced the costs of higher education for a limited number of students in the system. However, the policy was incapable of reversing the privatisation of the provision and costs dominant in the system. The policy created a regulated submarket with high public subsidies and higher regulations that coexist with an open university market, where high costs, low regulation and low public support remain dominant. The article is based on the qualitative analysis of policy documents and a descriptive analysis of quantitative data on public spending on higher education. The article finishes debating the challenges that the policy faces in the future and what aspects of higher education need to be changed to build public and free systems of higher education in Chile and other countries.